Відновлення спеціальних економічних зон в Україні: курс на реіндустріалізацію та структурну перебудову економіки у воєнно-повоєнному періоді - Підоричева, І.Ю.; Баш, А.С. (Економіка промисловості, 2025)
Обґрунтовано доцільність та умови відновлення діяльності спеціальних економічних зон в Україні як інструменту структурної перебудови економіки у воєнно-повоєнному контексті на основі аналізу вітчизняного та міжнародного досвіду їх функціонування, сучасних глобальних тенденцій їх розвитку під впливом Четвертої промислової революції. Розроблено пропозиції щодо доопрацювання змісту Глави 39 Господарського кодексу України в частині посилення економічних стимулів для інвесторів, які здійснюють виробничу діяльність у спеціальних економічних зонах, реалізація яких сприятиме підвищенню якості прийняття управлінських рішень щодо формування інвестиційних та інфраструктурних умов забезпечення економічної відбудови України. To implement structural changes in Ukraine’s economy, merely creating equal conditions for all economic activities is insufficient. It is necessary to introduce radical economic measures and effective, internationally proven, tools for economic development. These tools can enable the country to overcome the resource curse, deindustrialization, and break out of the vicious cycle of poverty. One such tool is the establishment of special economic zones (SEZ) – geographically delineated areas within a country’s national borders or border regions of multiple countries, characterized by special, more favorable regulatory and fiscal regimes and well-developed infrastructure. In Ukraine, special economic zones suffered a reputational setback due to the illegal activities associated with the Donetsk special (free) economic zone (S(F)EZ), which generated widespread negative perceptions of this instrument. However, the experience of other zones, particularly the Transcarpathian S(F)EZ, highlights the untapped potential of this tool in attracting foreign investment, stimulating industrial activity, creating jobs, and increasing tax revenues. This underscores the need to reassess the viability of using S(F)EZs as a mechanism for Ukraine’s economic reconstruction amidst the destruction and losses caused by wartime. The purpose of the article is to substantiate the feasibility and the conditions for reviving the activities of special (free) economic zones in Ukraine as a tool for reindustrialization and structural economic transformation in the wartime and post-war context. Achieving this purpose entails a critical analysis of the experience of economic zones in Ukraine and abroad, along with consideration of contemporary global trends in their development influenced by the Fourth Industrial Revolution. The theoretical foundation of the study is based on the developmentalist tradition, A. Serra's theory of uneven economic development, and F. List's theory of economic nationalism. The article outlines the historical evolution and modern global trends in the development of special economic zones. It is determined that a new generation of special economic zones is emerging, aligned with the requirements of the Fourth Industrial Revolution. These zones are characterized by their reliance on resource-efficient, energy-saving practices and the integration of digital technologies. Two key digital technologies driving the formation of modern industrial zones are digital twins and the metaverse. The adoption of these technologies enhances the innovativeness of industrial zones by optimizing costs and reducing the time required for modeling new production processes, prototyping, product testing, real-time monitoring of production efficiency at individual stages, and addressing operational challenges. The analysis of international experience in the operation of special economic zones has revealed key lessons essential for shaping effective policies for their development. Specifically, SEZs require an incubation period of 5–10 years (or even longer in developing countries) to achieve tangible economic outcomes. State support and the clear alignment of their objectives with the country’s core interests and strategic development priorities are critical factors for success. Additionally, SEZs must account for the realities of global competition by offering investors a comprehensive set of advantages, including not only fiscal incentives but also modern infrastructure, access to a highly skilled workforce, and streamlined business processes. The legal principles underpinning the support and development of S(F)EZs in Ukraine have been analyzed in greater depth. Proposals have been developed to refine Chapter 39 of the Economic Code of Ukraine, with a focus on strengthening economic incentives for domestic and foreign investors engaged in production activities in regions located near the front line, in de-occupied territories, or in areas affected by active hostilities. Implementing these proposals will enhance the quality of managerial decision-making related to creating favorable investment and infrastructure conditions, thereby contributing to the economic reconstruction of Ukraine.